Inertial-Sensor-Controlled Functional Electrical Stimulation for Swimming in Paraplegics: Enabling a Novel Hybrid Exercise Modality - Wiesener, Constantin; Seel, Thomas; Spieker, Lotta; Niedeggen, Andreas; Schauer, Thomas (IEEE Control Systems Magazine, 2020)
Here, we present initial results on an inertial sensor controlled neuroprosthetic system that supports people with spinal cord injuries during swimming exercises. This novel electrical stimulation system allows paraplegics to perform swimming exercises using their own legs.
CRIS-Team Scopus Importer:2021-03-31